Effects of Diosmin on Vascular Leakage and Inflammation in a Mouse Model of Venous Obstruction - Zou, Junjie; Yuan, Dongping; Yang, Jin; Yu, Yun (Frontiers in Nutrition, 2022)
At present, iliac vein compression syndrome (IVCS) plagues countless people, posing a significant economic and social burden. The progress of current IVCS-related research is slow owing to the limitations of animal models. In this study, we generated a mouse model of iliac vein stenosis (IVS) to monitor the effects of IVCS on venous function, such as increased vascular leakage, the expression of adhesion molecules, and elevated inflammation factors. Diosmin, a widely used clinical bioactive ingredient, was administered to confirm its therapeutic effects on the IVS mouse model. The results revealed that diosmin manifested therapeutic improvement in the IVS mouse model. In addition, we verified that the IVS mouse model is a stable and reproducible animal model for pathophysiological studies. High-purity diosmin can be beneficial to venous dysfunction and hence provides a more effective treatment option for venous diseases.